Breast reconstruction from the perspective of women submitted to mastectomy: A meta-etnography Reconstrução mamária sob a ótica de mulheres submetidas à mastectomia: Uma metaetnografia Reconstrucción mamaria bajo la óptica de mujeres sometidas a la mastectomía: Una metaetnografía - Volkmer C. (2019)
© 2019, Universidade Federal de Santa Catarina. All rights reserved.Objective: to analyze qualitative studies published in the national and international scientific literature on breast reconstruction after mastectomy for breast cancer, from the perspective of women. Method: systematic literature review using meta-ethnography, where the synthesis of knowledge is based on the induction and interpretation of the data found. Searches in the electronic databases identified 65 studies. 27 studides meet the inclusion and exclusion criteria. 13 studies compressed the analytical corpus of the review, according to the Critical Appraisal Skills Programme checklist. The data were synthesized by means of the meta-ethnographic approach. Results: the analyzed studies showed similarities regarding the women´s decision to perform breast reconstruction, the difficulty of choosing the type of surgery and to deal with the experience of the reconstruction, and that the women had difficulties in establishing relationships with certain health professionals, especially with doctors. They refer to the ambivalence of feelings regarding the expectations and results of breast reconstruction and complex process of “carrying on”. Conclusion: this review synthesizes the scientific knowledge regarding women’s perspective regarding the breast reconstruction process and highlights that health professionals must understand the perceptions of women undergoing mastectomy and breast reconstruction in order to improve the care provided.